Additive WO2 promotes Ni - based catalyst for hydrogen production from auto-thermal reforming of acetic acid. (1st May 2023) - Chen, Hui; Sun, Wenjing; Hu, Xiaomin; Wang, Qi; Wu, Tong; An, Shuang; Ding, Chenyu; Chen, Congmei; Huang, Lihong; Wang, Ning
Graphical abstract: Highlights: Ni-2W/SiO2 presents a promising hydrogen yield of 2.8 mol-H2 /mol-HAc in the ATR. The strong interaction of WO2 -Ni relieved carbon deposition and sintering of Ni 0 . The effect of electron donor by WO2 species preserved a stable proportion of Ni 0 . CH3 COOH tends to be enriched on the surface of WO2 of the WO2 /Ni(1 1 1) interface. Abstract: Nickel-based catalysts exhibit excellent initial activity in the auto-thermal reforming (ATR) of acetic acid (HAc) to produce hydrogen; meanwhile, deactivation issues, namely oxidation, sintering and carbon deposition, have not been fully addressed. Hence, we prepared a series of Ni–W/SiO2 catalysts and found the Ni-2W/SiO2 catalyst with 2 wt% W decoration presented the best catalytic activity and stability: the conversion rate of acetic acid was stable at 100 %, and the hydrogen yield remained at 2.8 mol-H2 /mol-HAc with neither sintering nor carbon deposition. The excellent catalytic performance of Ni-2W/SiO2 was analyzed and can be attributed to the special properties of WO2 as followed: First, during the ATR process, WO2 species migrated to the surface of Ni phase and formed an interface, which resulted in strong interaction of WO2 -Ni and relieved carbon deposition and sintering of Ni species; Second, the effect of electron donor by WO2 species on the WO2 -Ni interface during the reduction procedure was found and preserved a stable proportion of Ni 0 active species during the ATR process; Third, DFT and in-situ DRIFTS confirmed that CH3 COOH tends to be enriched on the WO2 species of the WO2 /Ni(1 1 1) interface rather than on the Ni(1 1 1) surface, promoting the adsorption and dehydrogenation of CH3 COOH to intermediates of CH3 COO* and H*, which is difficult to occur on WO3 species of the WO3 /Ni(1 1 1) interface because of high reaction barrier.